Influence of Brand Image, Product Quality, and Price on Yamaha Grand Filano Purchases - Kadek Mustika Putra Ady Suyasa; Sukmasari Triana Gita Putri; I Gusti Ayu Agung Istri Sari Dewi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The highly competitive market in motorbikes series, leads to fluctuation in sales of Yamaha Grand Filano. This study examines the influence of brand image, product quality, and price on consumer purchasing decisions for the Yamaha Grand Filano motorbike in Bali, especially at Yamaha Bisma Cokro. Using a quantitative approach with 80 respondents from purposive sampling and utilize multiple linear regression analysis, the study finds that brand image, product quality, and price each have a significant positive effect on purchasing decisions. A strong brand image enhances consumer trust and loyalty, high product quality encourages repeat purchases, and competitive pricing increases consumers’ preference for the Yamaha Grand Filano compared to competing products. These findings indicate that focusing on brand image development, maintenance product quality improvement, and appropriate pricing strategies can strengthen consumer confidence and help maintain market share. This study could be a recommendation for the company expansion and sales revenue generation.